El laboratorio experimental como estrategia didáctica para el aprendizaje de Organografía Vegetal en los estudiantes de cuarto semestre de la carrera de Biología Química y Laboratorio, período enero – agosto 2017. - Melena Tingo, Angie Katerine (2017)
The present research was developed at the National University of Chimborazo with the fourth semester students of the Biology, Chemistry and Laboratory Career in the Chair of Plant Organography demonstrating a deficient learning of the subject and use of the laboratory by students and teachers, a proposal for the implementation of the experimental laboratory was presented to develop this learning. The objective of the work is “To justify the influence of the experimental laboratory as a didactic strategy for the learning of Plant Organography in the students of the career”. The problema found arises from the need to strengthen the theoretical foundations related to this subject in students with learning problems, who have trouble to understand certain topics. The methodology was framed in the non-experimental study, of bibliographic type and field, being its descriptive level. The population was 18 students of the fourth semester of the career. To collect information, the questionnaire consisting of 10 multiple-choice questions was used as the survey technique and instrument. The main results are: 43% of students state that the experimental laboratory is not applied as a teaching-learning strategy of the Plant Organography, due to the limited availability of it. Therefore, the implementation of a new laboratory, appropriate to the subject, is recommended to strengthen not only the students´ learning through the execution of practices, but also the training of future professionals.